MyD88 mediates the decision to die by apoptosis or necroptosis after UV irradiation. Issue 5 (July 2014) - Harberts, Erin; Fishelevich, Rita; Liu, Juan; Atamas, Sergei P; Gaspari, Anthony A
UV irradiation-induced cellular damage is classically associated with apoptosis and is known to result in systemic immunosuppression. How the decision to undergo apoptosis is made following UV is not fully understood. We hypothesize that a central mediator of TLR signaling, MyD88, determines cell fate after UV exposure. Survival after UV of immortalized bone marrow-derived macrophages (BMDM) and ex vivo peritoneal macrophages (PM) from MyD88 germline-deficient mice (MyD88 -/- ) was significantly higher than wild type (WT) PM. UV-induced apoptosis (DNA laddering) in PM and epidermis of MyD88 -/- animals versus WT was decreased. In MyD88 -/- PM, decreased cleavage of caspase 3, as well as pro-necroptotic protein, RIP1, and a significant increase in transcription and release of pro-inflammatory TNF-α, suggest that necroptosis, rather than apoptosis, has been initiated. In vivo studies confirm this hypothesis after UV, showing low apoptosis by TUNEL and inflammation in MyD88 -/- skin sections. Considering that MyD88 participates in many TLR pathways, BMDM from TLR2 -/-, TLR4 -/- and WT mice were compared for evidence of UV-induced apoptosis. Only TLR4 -/- BMDM and PM had a similar phenotype to MyD88 -/-, suggesting that the TLR4–MyD88 axis importantly contributes to cell fate decision. Our study describes a new cellular consequence of MyD88 signaling after UV, and may provide rationale for therapies to mitigate UV-induced immunosuppression.